Associations between concussion and risk of diagnosis of psychological and neurological disorders: a retrospective population-based cohort study. Issue 3 (27th July 2020) - Morissette, Marc P; Prior, Heather J; Tate, Robert B; Wade, John; Leiter, Jeff R S
Abstract : Objective: To investigate associations between concussion and the risk of follow-up diagnoses of attention-deficit hyperactivity disorder (ADHD), mood and anxiety disorders (MADs), dementia and Parkinson's disease. Design: A retrospective population-based cohort study. Setting: Administrative health data for the Province of Manitoba between 1990–1991 and 2014–2015. Participants: A total of 47 483 individuals were diagnosed with a concussion using International Classification of Diseases (ICD) codes (ICD-9-CM: 850; ICD-10-CA: S06.0). All concussed subjects were matched with healthy controls at a 3:1 ratio based on age, sex and geographical location. Associations between concussion and conditions of interest diagnosed later in life were assessed using a stratified Cox proportional hazards regression model, with adjustments for socioeconomic status and pre-existing medical conditions. Results: 28 021 men (mean age ±SD, 25±18 years) and 19 462 women (30±21 years) were included in the concussion group, while 81 871 men (25±18 years) and 57 159 women (30±21 years) were included in the matched control group. Concussion was associated with adjusted hazard ratios of 1.39 (95% CI 1.32 to 1.46, p<0.001) for ADHD, 1.72 (95% CI 1.69 to 1.76; p<0.001) for MADs, 1.72 (95% CI 1.61 to 1.84; p<0.001) for dementia and 1.57 (95% CI 1.41 to 1.75; p<0.001) for Parkinson's disease. Conclusion: Concussion was associated with an increased risk of diagnosis for all four conditions of interest later in life.